Mortgage Securitization and Shadow Bank Lending - Gete, Pedro; Reher, Michael (Review of Financial Studies, 2021)
Abstract We show how securitization affects the size of the nonbank lending sector through a novel price-based channel. We identify the channel using a regulatory spillover shock to the cross-section of mortgage-backed security prices: the U.S. liquidity coverage ratio. The shock increases secondary market prices for FHA-insured loans by granting them favorable regulatory status once securitized. Higher prices lower nonbanks’ funding costs, prompting them to loosen lending standards and originate more FHA-insured loans. This channel accounts for 22% of nonbanks’ growth in overall mortgage market share over 2013–2015. While the shock creates risks for financial stability, homeownership also increases.